PROFIL PEMBINAAN EKSTRAKURIKULER OLAHRAGA PETANQUE DI SMA NEGERI 4 BANTAENG - Ria Ria; Ferawati Ferawati; Wahyu Munandar; Kurnia Rusli (Indonesian Journal Of Physical Activity and Sport Development (IJPASD), 2023)
Jumriani, 2023, Coaching Profile of Petanque Extracurricular of SMA Negeri 4 Bantaeng. Supervised by Ferawati and Kurnia Rusli. This research aimed to know the Coaching Profile of Petanque Sport Extracurriculars of SMA 4 Bantaeng. This research used descriptive research that aims to determine the profile of coaching petanque sports extracurricular at SMA Negeri 4 Bantaeng. Independent variable in this study was the physical condition, while the dependent variable is pointing and shooting skills. The sample of this research was 20 students. Data analysis techniques in this study using descriptive statistical techniques and calculation techniques using percentages. Based on the results of the research, it can be concluded that physical condition of pointing and shooting abilities of SMA Negeri 4 Bantaeng including medium category. The physical condition of students was moderate of 100%. Meanwhile, the ability to point and shoot is in the moderate category by 35%. This shows that the extracurricular coaching profile of petanque at SMA Negeri 4 Bantaeng on pointing ability and shooting is medium category.